Legal and Ethical Issues of Organ Transplantation in Pakistan A Critical Appraisal in Sharī‘ah’s Perspective - Irfan Qaisar; Sadia Manzoor; Dr. Mohyuddin Hashmi (MEI, 2023)
Organ Transplantation is one of the significant development in the area of medicine and practiced in almost every region of the world in order to save the lives of sick individuals. Due to the excessive demand of organs and shortage of availability, many of the complex legal, ethical and religious issues have been aroused in this field. Pakistan is viewed as one of the leading country in the world for transplant tourism, illegal buying and selling of organs particularly commercial renal transplantation and organ trafficking. The objective of this article is to highlight the illegal and unethical practices of organ transplantation prevailing in Pakistan and to critically appraise such practices in Shari’ah’s perspective. In addition the aim of research is to spread light on the Shari’ah’s ruling pertaining to organ transplantation and strict prohibition of organ trafficking and alike practices. The methodology of research is descriptive, analytical, and applied. The information is collected from books, scholarly articles, conference proceedings, seminar paper presentations and internet sources. In the end research made recommendation that government should take measures keeping in view the principles of Shari’ah in order to deal with the issues of transplantation tourism illegal selling and buying and organ trafficking. Additionally there is a dire need to monitor and regulate the practices of organ transplantation in the country by the government.